20 jaar Galerie Amaryllis 1980-2000. - Galerie Amaryllis, Brussel; Bayes, Joe (Brussel : Galerie Amaryllis, 2000)
Batbedat, Vincent ; Bezie, Charles ; Brams, Maurice ; Bude, Cécile ; Coppieters 't Wallant, Chantal ; Crombé, Patrick-Frederick ; Decock, Gilbert ; de Kort, Jet ; Delbrassinne, Elise ; D'Haese, Begga ; Dries, Jan ; Dusepulchre, Francis ; Dijck, Ward ; Gangolf, Serge ; Germonpre, Gerrit ; Lambele, Antonia ; Leblanc, Walter ; Lixenberg, Cyril ; Peire, Luc ; Pérez-Flores, Dario ; Popet, Yves ; Prosi, Henri ; Ramon, Renaat ; Reychler, Rita ; Rohr, Renée ; Seuphor, Michel ; Strack, Walter ; Vandenbranden, Guy ; Van Praet, Remi ; Van Putten, Henk ; Van Sumere, Hilde ; Vermeulen, Noël ; Zerep
biografie
20 jaar Galerie Amaryllis 1980-2000, Galerie Amaryllis, Brussel, 7 oktober - 19 november 2000
Nederlands & Frans
boek